2012
DOI: 10.2478/v10045-012-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Azadirachtin, Cypermethrin, Methoxyfenozide and Pyridalil on Functional Response of Habrobracon Hebetor Say (HYM.: Braconidae)

Abstract: Abstract:Habrobracon hebetor Say is one of the most important natural enemies of the Helicoverpa armigera Hübner (Lep.: Noctuidae). In this study, the sublethal effects of LC 30 concentration of azadirachtin, cypermethrin, methoxyfenozide and pyridalil on the functional response of H. hebetor to different densities of 5th instars larvae of Ephestia kuehniella Zeller were evaluated. Young females were exposed to LC 30 of the insecticides for an appropriate time of exposure. Then, six randomly selected alive fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…These results agreed with that obtained by Vahid Mahdavi (2013) who showed that spinosad and abamectin are less toxic than carbaryl and thiodicarb on B.hebetor. The results also confirm the results of Abedi (2012), who reported that biological pesticides had less of an impact on natural enemies. Also, Reddy et al (1997) reported that insecticide treatments with 5 different at different concentrations, were ranked slightly harmful to harmful after 48 hours post treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results agreed with that obtained by Vahid Mahdavi (2013) who showed that spinosad and abamectin are less toxic than carbaryl and thiodicarb on B.hebetor. The results also confirm the results of Abedi (2012), who reported that biological pesticides had less of an impact on natural enemies. Also, Reddy et al (1997) reported that insecticide treatments with 5 different at different concentrations, were ranked slightly harmful to harmful after 48 hours post treatment.…”
Section: Discussionsupporting
confidence: 90%
“…This parasitoid can easily be mass reared and released in the open fields for control of many lepidopteran insects. Integration between chemical pesticides and bio-control agents were used in Integrated Pest Management programs as mentioned by Zhao (2000) and Abedi (2012). Application of chemical control should be used only when it is necessary and when it can be least disruptive to biological control (Jepson, 1989;Rafiee-Dastjerdi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of pesticides on functional response can contribute to the success of IPM programs and to the release of the natural enemies (Abedi et al 2012). The results of this study indicated that there was a type III functional response of E. mundus in response to host density in imidacloprid treatment as well as the control.…”
Section: Discussionmentioning
confidence: 65%
“…In type III, the response curve rises in a sigmoid manner to a plateau. Studies on the effects of pesticides on the functional response of natural enemies are scarce (Perera 1982;Claver et al 2003;Poletti et al 2007;Rafiee Dastjerdi et al 2009;Abedi et al 2012). The chloronicotinyl insecticide, imidacloprid, and the insect growth regulator (IGR), buprofezin, are two relatively new insecticides for controlling whiteflies in Iran (Talebi-Jahromi 2007).…”
mentioning
confidence: 99%
“…The obtained parasitoids urgently were transferred to laboratory conditions at 25 ± 1 °C, 60 ± 5% relative humidity (RH) and photoperiod of 16:8 (L:D) h and were reared on the larvae of flour moth (Ephestia kuehniella Zeller) as its laboratory host. During the rearing processes, the honey solution (10%) was used for feeding of this biocontrol agent (Rafiee-Dastjerdi et al 2008, 2009a, 2009bMahdavi 2013;Abedi et al 2012Abedi et al , 2014Asadi et al 2018a).…”
Section: Rearing Of Biological Control Agentmentioning
confidence: 99%